2011
DOI: 10.3892/or.2011.1231
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three distinct methods for the detection of circulating tumor cells in colorectal cancer patients

Abstract: Abstract. the detection of circulating tumor cells (ctcs) has considerable utility in the clinical management of patients with solid cancers. However, the phenotypic heterogeneity of ctcs and their low numbers in the bloodstream of patients means that no standardized detection method currently exists for these cells. this, together with differences in pre-analytical sample processing, has led to the collection and accumulation of inconsistent data among independent studies. Here, we compare the ability of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…However, another study has revealed that the AdnaTest BreastCancer™ has equivalent sensitivity to that of the CellSearch in detecting two or more CTC [40]. Moreover, recent studies, especially in early breast cancer, have also shown a superior sensitivity of molecular assays with respect to the CellSearch [11,21,25,28]. In most of these comparison studies, discrepancies found between the different assays were partly explained by the fact that these molecular assays were using different capture technologies for CTC isolation and very different detection systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study has revealed that the AdnaTest BreastCancer™ has equivalent sensitivity to that of the CellSearch in detecting two or more CTC [40]. Moreover, recent studies, especially in early breast cancer, have also shown a superior sensitivity of molecular assays with respect to the CellSearch [11,21,25,28]. In most of these comparison studies, discrepancies found between the different assays were partly explained by the fact that these molecular assays were using different capture technologies for CTC isolation and very different detection systems.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial cell adhesion molecule (EpCAM) expression was approximately 10-fold lower on CTCs compared to on primary and metastatic tissues, suggesting that it is dependent on the local microenvironment and is down-regulated on CTCs [ 31 ]. This may be the reason why CTCs were undetected by the CellSearch™ System in a significant proportion of patients with CRC [ 32 ]. Although the CellSearch™ is the only FDA-approved technology applied for CTC enrichment, it cannot capture non-epithelial CTCs, such as the CTCs that have undergone EMT, resulting in a missed detection.…”
Section: Origins Merits and Demerits Of Ctcs/ Ctdna/ Exosomesmentioning
confidence: 99%
“…[5], [6] However, heterogeneous results have been obtained when comparing CTCs enumerated in the same patient blood samples using different CTC detection technologies. [7][11] …”
Section: Introductionmentioning
confidence: 99%